On the vertical distribution of mean point velocities in open channels - Paz Martínez, Javier (Revista Universidad de Guayaquil, 1991)
In the present work, a brief review of different investigations and proposals is presented, to determine the vertical distribution of the mean point velocities in open channels and the Karman coefficient, a parameter of the most widespread logarithmic type formula, concluding that the proposals are schematic. and they do not reflect what is observed in nature and were also carried out for two-dimensional flows excluding important factors such as the shape of the cause, properties and turbulence index, so the problem remains open and deserves investigative dedication.